The overprotective parent: Bureaucratic agencies and natural hazard management - Paul A. Raschky (University of Innsbruck, Department of Public Finance, 2007)
Due to the public good character of protective measures against natural disasters events, their allocation is very often in the realm of bureaucratic and expert agencies. Based on the economic theory of bureaucracy the behavior of a bureau providing the good protection against natural hazards is analysed. The existing model is extended by further institutional constraints accounting for societal controll mechanisms. The main proposition is that the allocation of protective measures through natural-hazard-management-agencies does also result in cost and allocative inefficiencies, however, the amount of allocative inefficiencies is relatively higher as compared to a normal bureau. This is mainly due to the potential of blame-shifting from politicians to bureaucrats. The considerations made in this paper can help to design a more efficient institutional framework in societal natural hazard management.
Keywords: D72; D73; D81; Q54; 330; theory of bureaucracy; natural hazards; blame-shifting; Bürokratietheorie; Naturkatastrophe; Katastrophenhilfe